Revisiting the South African book market: towards a change of tongue? - Morgan, Naomi (University of the Free State, 2006)
In this overview of the South African book market, based on publications until July 2006, the publication of novels is divided into three language categories: English, Afrikaans and African languages. As regards the last two categories, a multilingual book market with the possibility of being translated into the world’s most important literary languages, would be considered ideal. Historical, social and personal reasons for choosing a language other than the writer’s mother tongue are investigated. A tendency amongst writers from these language groups to write or to begin writing in English solely for financial reasons is also investigated.

In hierdie oorsig van die Suid-Afrikaanse boekemark gebaseer op bronne tot en met Julie 2006, word die publikasie van romans verdeel in drie taalkategorieë: Engels, Afrikaans en Afrikatale. Wat laasgenoemde twee kategorieë betref, word ’n meertalige boekemark met ’n sterk vertalingskultuur na die belangrikste literêre tale van die wêreld, as ’n ideaal gestel. Historiese, sosiale en persoonlike redes waarom skrywers verkies om in ’n ander taal as hul moedertaal te skryf, word ondersoek. Daar word gewys op ’n tendens onder skrywers uit hierdie taalgroepe om suiwer om finansiële redes in Engels te skryf of te begin skryf.
Keywords: South Africa; Book market; Publication; Novels; English; Afrikaans; African languages; Multilingual book market